Amelioration of Single Clove Black Garlic Aqueous Extract on Dyslipidemia and Hepatitis in Chronic Carbon Tetrachloride Intoxicated Swiss Albino Mice - Gia-Buu Tran; Sao-Mai Dam; Nghia-Thu Tram Le (International Journal of Hepatology)
Single clove garlic is the product of atypical bulbing process of garlic under specific conditions. Therefore, the number of researches on single clove garlic bioactivity is limited. Recently, the hepatoprotective effect of single clove garlic has been demonstrated. In this study, we investigated amelioration of single clove black garlic aqueous extract, a processed product from single clove garlic, on dyslipidemia and hepatitis induced by chronic administration of CCl4. Mice were randomly divided into four groups: control, extract control, CCl4 intoxication, and coadministrated CCl4 and extract group. Mice were orally given a dose of 1 ml/kg body weight of CCl4 for 28 days twice a week to establish chronic liver injury model. To evaluate the hepatoprotective effect of single clove black garlic, mice were cotreated with CCl4 and single clove black garlic extract (200 mg/kg body weight) via gastric gauge for 30 days. Cotreatment with CCl4 and extract could improve the changes of body weight, liver weight, and relative liver weight as compared to CCl4 intoxicated mice. Single clove black garlic ameliorated dyslipidemia and the elevation of ALT and AST levels induced by chronic CCl4 intoxication. Histological studies revealed that single clove black garlic could prevent mononuclear cells infiltration and hepatocyte necrosis.